A specific Toll‐like receptor profile on T lymphocytes and values of monocytes correlate with bacterial, fungal, and cytomegalovirus infections in the early period of allogeneic stem cell transplantation. Issue 5 (12th July 2014) - Skert, C.; Fogli, M.; Garaffa, E.; Perucca, S.; Fiorentini, S.; Cancelli, V.; Turra, A.; Ribolla, R.; Filì, C.; Malagola, M.; Bergonzi, C.; Cattina, F.; et al.
Abstract Background Bacterial, fungal, and viral infections often affect non‐relapse mortality after allogeneic stem cell transplantation (alloSCT). Recovery from infections depends on a balanced integration between innate and adaptive immune responses. In this complex interplay, a key role is played by Toll‐like receptors (TLRs), which are sensors of pathogen‐associated molecular patterns. To our knowledge, no previous study deals with both expression and function of all human TLRs together, in relation to infections in the setting of alloSCT. Methods We prospectively evaluated 9 TLRs by flow cytometry on T lymphocytes and monocytes of 35 patients in relation to infectious events from day +30 to day +120. Tumor necrois factor‐alpha, interleukin‐4, interferon‐gamma, and monocyte chemoattractant protein‐1 induction upon TLR activation was assessed by enzyme‐linked immunosorbent assay on cell supernatants. Results In multivariate Cox regression analysis, levels of TLR‐9 expression on T lymphocytes (P = 0.01) and values of natural killer cells (P = 0.01) correlated negatively with bacterial infections, whereas cytomegalovirus (CMV) infection resulted as a positive predictor. We observed a trend for negative correlation between TLR‐7 levels on T lymphocytes and fungal infections (P = 0.07). Values of monocytes were negatively associated with CMV infection (P = 0.03), whereas levels of TLR‐5 on T lymphocytes were positive predictors (P = 0.01). Age (P = 0.03) and bacterial infections (P = 0.006) negatively influenced overall survival. Monocyte values were positive predictors of survival (P = 0.003). Conclusions Bacterial, fungal, and CMV infections were associated with a different expression of some TLRs on T lymphocytes. The protective role of TLR‐7 and TLR‐9 seemed dominant over other TLRs involved in recognizing fungi and bacteria. We also observed an atypical involvement of TLR‐5 in CMV infection. The dominant and atypical role of some TLRs could depend on their pleiotropic functions and the changing inflammatory environment of transplanted patients. A specific TLR profile and an adequate count of monocytes could improve survival, promoting an effective control of infections, and balanced immune responses. If our findings will be confirmed by further studies, these immunological variables could be useful as parameters to predict susceptibility to infections.